2018
DOI: 10.3892/ijo.2018.4429
|View full text |Cite
|
Sign up to set email alerts
|

E2F1/SP3/STAT6 axis is required for IL-4-induced epithelial-mesenchymal transition of colorectal cancer cells

Abstract: Colorectal cancer (CRC) is a type of cancer with a mortality rate among the highest worldwide owing to its high rate of metastasis. Therefore, inflammation-associated metastasis in the development of CRC is currently a topic of considerable interest. In the present study, the pro-inflammatory cytokine interleukin-4 (IL-4) was identified to promote the epithelial-mesenchymal transition (EMT) of CRC cells. However, the enhancing effect of IL-4 was more evident in HCT116 cells compared with in RKO cells. Accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 37 publications
1
59
0
Order By: Relevance
“…4C ; P<0.001). Following examination of previous literature, it was noted that E2F1 serves a crucial role in CRC and is an important molecular regulator upstream of p21 ( 20 , 21 ). Therefore, it was hypothesized that E2F1 may participate in the regulation of p21 expression by CDCA3.…”
Section: Resultsmentioning
confidence: 99%
“…4C ; P<0.001). Following examination of previous literature, it was noted that E2F1 serves a crucial role in CRC and is an important molecular regulator upstream of p21 ( 20 , 21 ). Therefore, it was hypothesized that E2F1 may participate in the regulation of p21 expression by CDCA3.…”
Section: Resultsmentioning
confidence: 99%
“…The role of STAT6 in cancer has recently been studied; there are studies in colorectal cancer, prostate cancer, glioblastoma, gastric cancer, and breast cancer that indicate that STAT6 may have an important role in the growth, aggressiveness, resistance to apoptosis, epithelial to mesenchymal transition, and metastasis of cancer cells [ 145 , 146 , 147 , 148 , 149 ]. However, some research groups suggest that STAT6 is necessary to inhibit growth and to mediate apoptosis via IL-4 in melanoma, colorectal, and breast cancer cells [ 150 , 151 , 152 ].…”
Section: Jak/stat Pathway and Cervical Cancermentioning
confidence: 99%
“…Moreover, some reports have indicated that STAT6 overexpression plays a critical role in promoting EMT and aggressiveness of CRC through Zinc-finger E-box binding homeobox 1 (ZEB1) activation, which is currently considered as a factor associated with chemoresistance [56]. In line with this, we found that STAT6 regulates SNAI1, another typical marker of EMT, which has an important role in E-cadherin expression and that the levels of SNAI1 were inversely related with E-cadherin expression, as reported in esophageal cancer [47].…”
Section: Discussionmentioning
confidence: 99%